Translation Analysis of Romanticism In 50 First Dates Movie - Robi Aji Sugihartono; Muh. Aprianto Budie Nugroho; Yuniarti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
50 First Dates is a movie that broadly known around the globe in 2004 as one of the best romantic comedy movie in the 2000s. This research aims to analyze type of romanticism and the translation techniques used in the 50 First Dates movie subtitle in Amazon Prime Video. This research uses qualitative method with case study as a research design. This research uses document analysis with transcript and subtitle of the movie. The data are analyzed using theory from Lomas (2018) in finding the type of romanticism and theory by Molina and Albir (2002) to find out the types of translation techniques. Based on findings, there are 6 types of love found out of 14, namely: Philia (31.03%), Storge (25.28%), Paixnidi (21.83%), Ananke (13.79%), Epithymia (5.74%) and Pragma (2.29%). Regarding the translation techniques, 9 out of 18 types of translation techniques are found, namely; Established Equivalent (47.61%), Linguistics Compression (15.87%), Borrowing (8.73%), Reduction (8.73%), Compensation (7.93%), Linguistics Amplification (4.76%), Modulation (3.17%), Amplifications (2.38%) and Particularization (0.79%). Based on the data, the researcher found that the translation used more than one translation techniques. Therefore, the researcher grouped them into single (59.77%), duplet (31.03%), triplet (8.04%), and quadruplet group (1.14%). From the findings, it can be concluded that the most found type of love is Philia. On the other hand, the most dominant type of translation techniques is Established Equivalent with various combinations.